Motor development delay in offspring is associated with prenatal telbivudine exposure. Issue 9 (March 2018) - Zhou, Chengliang; Yu, Ying; Yang, Qian; Wang, Huihui; Hou, Min; Jin, Li; Zhang, Fanghong; Sheng, Jiangzhong; Miao, Mingfang; Yang, Xiaofu; Huang, He-Feng
Abstract : Abstract: Telbivudine is an orally nucleoside analog with potent and specific antihepatitis B virus (HBV) activity, and it has been reported to block mother-to-infant transmission. However, few studies have focused on the safety of prenatal exposure for offspring development. This is a prospective noninterventional study. Participants were enrolled during delivery through the Women's Hospital of Zhejiang University School of Medicine between January 2012 and September 2013. Neonate's umbilical cord arterial blood (UCAB) was collected after delivery. Hepatitis B virus DNA copy, HBV serology, alanine aminotransferase (ALT), creatine kinase (CK), creatinine (CRE), and blood urea nitrogen (BUN) were measured. The development of the offspring was evaluated by the Chinese Revision of Bayley Scales of Child Development (BSCD-CR) at 12 to 24 months old. Around 30 and 31 chronic hepatitis B mothers were recruited in untreated group (non-LdT group) and telbivudine-treatment group (LdT group), respectively, and 2 children (one in non-LdT group and 1 in LdT group) were lost in follow-up. Sixty-one normal women and their children were recruited as a normal control (control group). Compared with non-LdT group, telbivudine treatment effectively blocks HBV transmission from mother to infant. However, CK in UCAB was significantly increased in the LdT group. Moreover, children with prenatal telbivudine exposure showed lower level of serum creatinine than non-LdT group, reduction of psychomotor developmental index and increased risk of motor development delay. Prenatal telbivudine exposure is correlated with motor development delay in offspring. Abstract : Supplemental Digital Content is available in the text